A simple external tissue expansion technique based on viscoelastic properties of skin to attain direct closure of a large scalp defect: A case report - Bandikatla Venkata Ratnam (Indian Journal of Plastic Surgery, 2015)
Background: Direct closure of large scalp defects is not an easy task. Complicated flap designs or staged surgeries over a period of 6 months are often required. A case of a large scalp defect that was closed directly in 3 months by applying a simple external tissue expansion technique is presented in this report. Patient Profile: A 28-year-old male patient presented with a painful swelling of about 13 cm × 14 cm, on frontoparietal scalp. A biopsy done elsewhere reported it to be a neurofibroma. He sought tumour excision and scalp defect coverage by hair-bearing scalp in a period of less than 5 months. Materials and Methods: The tumour was excised and the adjacent scalp was gradually expanded with the help of an external fixator. The patient had immediate pain relief after excision. The goal of repairing scalp defect and replacing it with hairy scalp was achieved in 3 months. Conclusion: The mechanical device required for this technique is relatively easily accessible. It is not difficult to achieve desirable outcomes, and the same can be applied to large wounds on other areas.